TEMPORAL CORRELATIONS BETWEEN OPTICAL AND GAMMA-RAY ACTIVITY IN BLAZARS - Cohen, Daniel P.; Romani, Roger W.; Filippenko, Alexei V.; Cenko, S. Bradley; Lott, Benoit; Zheng, WeiKang; Li, Weidong (The Astrophysical journal, 2014)
We have been using the 0.76 m Katzman Automatic Imaging Telescope (KAIT) at Lick Observatory to optically monitor a sample of 157 blazars that are bright in gamma-rays being detected with high significance (10[sigma]) in one year by the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope. We attempt to observe each source on a three-day cadence with KAIT, subject to weather and seasonal visibility. Using the discrete correlation function (DCF), here we search for temporal relationships between optical and gamma-ray light curves in the 40 brightest sources in hopes of placing constraints on blazar acceleration and emission zones. A stacked average DCF of the 40 sources verifies this correlation trend, with a peak above 99% significance indicating a characteristic time delay consistent with 0 days. The findings strongly support the widely accepted leptonic models of blazar emission. It is clear that long-term monitoring at high cadence is necessary to reveal the underlying physical correlation.